Effects of fish silage on growth and biochemical characteristics of fresh water microalga Scenedesmus sp. MB 23 - Abdulsamad, Jasmin Kaippilliparambil; Varghese, Saramma Aikkarakunnath (Agriculture and Natural Resources, 2017)
Scenedesmus sp. MB 23 was cultivated in fish silage to study the effects of different concentrations on the growth and biochemical characteristics, particularly the protein, carbohydrate and lipid properties. Fish silage with 12% concentration was most effective for the growth and biomass production of Scenedesmus sp. The microalga reached maximum cell density (2433.89 x 104 cells/mL), chlorophyll-a concentration (2.766 µg/mL), specific growth rate (0.48/d) and biomass (2.73 g/L) on this medium. In mass culture, enhanced production of protein (123.87 mg/g dry weight of alga), carbohydrate (44.904 mg/g dry weight of alga) and lipid (84.21 mg/g dry weight of alga) was found using 9% fish silage. The effective reduction (up to 90%) in the concentrations of nitrate, phosphorus and ammonia in the final fish silage medium proved the removal efficiency of Scenedesmus sp. The enhanced production of Scenedesmus sp. MB 23 indicated that effective bioremediation of fish waste can be conducted using algal mass production in fish silage. The study also proved that microalgae grown in fish silage have great industrial potential and can be used as a source of feed and biofuel.